The Dyffryn Clwyd Court Roll Project, 1340-1352 and 1389-1399: a methodology and some preliminary findings - Barrell, Andrew D. M. (Medieval society and the manor court, 1996)
Court rolls are one of the premier sources for an understanding of Marcher lordship and society. Since the March of Wales stood outside the normal ambit of English government and jurisdiction, historians will find very little useful information in the central records of the English kingdom. Instead, reliance has to be placed on the records of the Marcher lords themselves, supplemented by scattered collections of deeds and vernacular poetry. The lordship of Dyffryn Clwyd was one of the forty or so Marcher lordships of Wales in the later Middle Ages. The Dyffryn Clwyd court rolls were discovered in 1854, in a loft above the Town Hall at Ruthin. In number and chronological age, there are 187 individual rolls, covering the period from 1294 to 1654. This chapter focuses on the challenges and opportunities which its court rolls present to the historian. It discusses the Dyffryn Clwyd court rolls project, which examined the court rolls for the periods 1340-52 and 1389-99.